Nitritação parcial de abate de aves em reator em batelada sequencial e reator de fluxo contínuo - Assis, Tatiane Martins de (2013)
The poultry slaughter industries have been producing an effluent with nitrogen which, when released in watercourses, can have strong impact on natural environments. Mostly, the conventional treatment systems are not able to remove nutrients in the right levels that are demanded by Brazilian legislation. Therefore, it is necessary to adopt post-treatment mechanisms to remove those composts. Thus, the present study aimed at evaluating and comparing both reactors performance concerning partial nitritation with a sequential batch reactor and a continuous flow one, whose biomass is under suspension at pre-ANAMMOX treatment using poultry slaughter effluent. Two reactors were used in this trial: the first model is in the sequential batch, in which the time reductions in cycle of 24, 16, 6, 5 and 4 hours were tested as a mechanism of nitrite-oxidizing bacteria inhibition. The conditions of low concentration of dissolved oxygen, ammonia inhibition or restriction of free alkalinity were also associated in this process. While, nitrite-oxidizing organisms Inhibition was achieved with a 4 hour time cycle, with low dissolved oxygen concentration (0.3 to 0.5 mg.L-1) and supplying alkalinity as carbonates and bicarbonates to 50% ammonia oxidation (restriction alkalinity). A four hour time was not enough to achieve 50% oxidation of ammonia. Then, there were partial nitritation tests according to time, consequently such cycle time reached up an average of 6.03 ± 0.63 hours. So, the continuous flow reactor started working with the best batch conditions, which was operated with a 6 hour HRT, SSV in 2700 mg.L-1 inoculation and 0.015 L.h-1 recycle flow. When the data removal began, the reactor showed a nitrate accumulation as a strategy to inhibit nitrite-oxidizing bacteria, so, there was a reduction in SSV to 1500 mg.L-1, which was effective to inhibit nitrite-oxidizing organisms. But, during the 40 days of operation, the continuous flow reactor did not show stable behavior concerning the effluent attainment as compared to 50% ammoniacal nitrogen and 50% nitrite, available in the pre-ANAMMOX affluent.